Strategi Adaptasi Mahasiswa Muna Dalam Kehidupan Kampus di Universitas Negeri Manado - Leoni Leoni; Sangputri Sidik; Hamsah Hamsah (PT. Citra Media Publishing, 2026)
This study examines the socio-cultural adaptation process of Muna students in campus life at Universitas Negeri Manado. As migrant students, Muna students arrive with relatively homogeneous cultural backgrounds, strong religious values, and social habits that differ from the multicultural campus environment. This research employs a qualitative approach using a case study method. Data were collected through in-depth interviews and analyzed using thematic analysis involving data reduction, data display, and conclusion drawing. The findings reveal three main themes. First, the decision to pursue higher education outside their home region is driven by family encouragement, the desire to broaden knowledge, and the motivation to gain cross-cultural experiences. Second, students experience cultural shock during the early stages of university life, particularly related to language differences, communication styles, and patterns of social interaction. However, these challenges are temporary and gradually diminish through increased social engagement. Third, the adaptation process occurs through identity negotiation, in which students adopt selective adaptation strategies by maintaining their cultural values while adjusting to the new environment. The study concludes that migrant student adaptation is a dynamic process that does not lead to full assimilation but rather to the formation of a hybrid identity, enabling students to function socially in a multicultural setting without losing their cultural roots. These findings highlight the importance of institutional support from universities in fostering social integration and cultural diversity on campus.